Vaccination efficacy against post-COVID-19 symptoms in Delta and Omicron waves: a prospective cohort in East Indonesia - Nur Upik En Masrika; Aryandhito Widhi Nugroho; Pramon Viwattanakulvanid; Bumi Herman (International Journal of Public Health Science (IJPHS), 2023)
The post COVID-19 symptoms affect the productivity and the quality of life among survivors. It is imperative to identify the effect of virus variants and the vaccination against post-COVID-19 symptoms. There were 242 participants from the eastern part of Indonesia diagnosed with COVID-19 during July 2021-July to 2022 were recruited online. The participants underwent data collection and semi-clinical follow-up for post-COVID-19 symptoms within 30 days after the first symptoms or from the diagnosis day using a validated clinical questionnaire and physician confirmation. Fatigue was the most reported post-COVID-19 symptom (27.7%), followed by chronic cough (21.5%) and headache (15.3%). Adjusted by confounding factors in hierarchical logistic regression, the differences in post-COVID-19 symptoms were insignificant across different variants. Regarding vaccine efficacy against three post-COVID-19 symptoms, people with two-dose vaccination significantly reported lower post-COVID-19 chronic cough (adjusted Odds Ratio 0.244 95% CI OR 0.071-0.838), but the protection against fatigue and the chronic headache was insignificant. There is an indication that vaccine efficacy may be waning along with the emerging new variants.